Two new species of Amphinemura (Plecoptera: Nemouridae) from southwestern China - Yan, Yanhua; Li, Mengyu; Yang, Ding; Li, Weihai (Zootaxa, 2022)
Two new species of nemourid stonefly, Amphinemura daloushana sp. nov. and A. liui sp. nov., are described from Chongqing municipality of southwestern China. The relationships between the new species and similar species in the genus are discussed.